Strategy of Conserving Karawitan in Studio Seni Lombang Sarwi Tuwel Village, Tegal Regency (Universitas Negeri Semarang, 2023)
Studio Seni Lombang Sarwi which is located in Tuwel Village, is unique in that it has musical lessons specifically or targeted at teenagers in the village. This activity is of course as a filler for children's free time so that it is used for useful activities compared to playing gadgets and without parental supervision, it will have a negative impact. In this thesis research, researchers used a phenomenological approach and used qualitative methods. Data collection is done through observation, interviews and documentation. In the data validity technique using the triangulation technique. The results of this research are the preservation strategy used, namely by using staging media and media. Based on the results of the research and discussion related to the strategy for preserving karawitan of studio Lombang Sarwi, the following conclusions can be drawn: the strategy used by the Lombang Sarwi in the effort to preserve musical instruments is by using staging media and through visits. Through a musical performance played by teenagers, it will attract the interest of their friends to participate in playing karawitan music, this is because those who watch the performance of their friends feel motivated to be able to do the same thing. In addition to encouragement from the teenage audience, parents who have children will also be motivated because they are motivated so that their children can also have positive activities, so they advise their children to fill their free time to learn karawitan music at the Lombang Sarwi. Then by providing the best presentation when there is a visit, it is hoped that it can make the visitors interested and the most important thing is to give the impression of an interesting experience during a visit to the Lombang Sarwi Art Studio. That way the visitors after leaving the studio will bring this impression to the wider community and share their experiences during a visit to the Studio Seni Lombang Sarwi.